2018
DOI: 10.1111/spc3.12381
|View full text |Cite
|
Sign up to set email alerts
|

Lay theories of willpower

Abstract: Some people believe that willpower relies on a limited resource and that performing cognitive work (such as using self-control) results in mental fatigue. Others believe that willpower is nonlimited and that performing cognitive work instead prepares and energizes them for more. These differing lay theories of willpower determine whether or not one's self-control performance actually does decrease or increase after use, with only limited willpower theorists showing a decrease (the ego depletion effect). Due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 57 publications
(92 reference statements)
2
35
0
Order By: Relevance
“…One possible reason for such mismatches between effort and subjective fatigue may be that sometimes exerting effort does not feel effortful. In line with others (e.g., Clarkson et al, 2010;Job, Dweck, Dalton, 2010;Francis & Job, 2018), we suggest that fatigue is a matter of perception. Importantly, we propose that people will not feel depleted when they are engaged in an interesting or enjoyable activity, even if it is objectively demanding.…”
Section: Phenomenology Of Fatiguesupporting
confidence: 92%
“…One possible reason for such mismatches between effort and subjective fatigue may be that sometimes exerting effort does not feel effortful. In line with others (e.g., Clarkson et al, 2010;Job, Dweck, Dalton, 2010;Francis & Job, 2018), we suggest that fatigue is a matter of perception. Importantly, we propose that people will not feel depleted when they are engaged in an interesting or enjoyable activity, even if it is objectively demanding.…”
Section: Phenomenology Of Fatiguesupporting
confidence: 92%
“…For example, Job et al, showed that whether or not individuals were prone to ego depletion depended on their own implicit theories regarding the limits of self-control (2010) (Job, Dweck, & Walton, 2010): If self-control was conceived as unlimited, no ego depletion effect was observed. Francis andJob (Francis &Job, 2018) (2018) suggest that such implicit theories "affect how mental work is processed […] [and] might change the expected value of a self-control task, including its feasibility and desirability (p. 8)."…”
Section: Less Performance Impairment When Person-situation Fit Is Supmentioning
confidence: 99%
“…OAK severity was measured with the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC; [22]). Patients responded to 24 items on an 11-point scale ranging from "no symptoms" (0) to "extreme symptoms" (10). Three subscales specified symptomatology regarding (1) pain (e.g., "Please enter the amount of pain you have experienced in the past 48 hours while walking on a flat surface"), (2) stiffness (e.g., "How severe is your stiffness after first awakening in the morning?…”
Section: Severity Of the Osteoarthritis Of The Kneementioning
confidence: 99%
“…A growing body of research indicates that individual differences in self-control performance depend on people's beliefs about the availability of self-control resources, colloquially called willpower [9,10]. According to this research, people differ in whether they believe that willpower is easily depleted and needs to be refueled after a demanding task (i.e., believing in limited willpower) or that willpower is rather nonlimited resource (i.e., believing in nonlimited willpower) that is not easily used up or can even be replenished when people exert self-control [11].…”
Section: Introductionmentioning
confidence: 99%